Comparative analysis of decision-making factors of hybrid and emission-free heat source users in single-family houses - Nadolny Michał; Walaszczyk Ewa; Walerysiak Sebastian (Journal of Economics and Management)
Aim/purpose – Energy is traditionally produced using fossil fuels as raw materials, which impacts the environment negatively. Due to the scarcity of fossil fuel supplies, rising prices of energy carriers, and global trends, consumers are turning to renewable energy sources (RES) for home heating. The aim of this study was to determine whether the choice of house heating system using different sources than fossil fuels is driven by any additional components of single-family house users’ purchasing decisions besides cost. Based on research results, the prospects for further transformation of thermal energy in single-family housing in Poland towards RES were determined.